Efficient synthesis of organic semiconductors by Suzuki–Miyaura coupling in an aromatic micellar medium. Issue 16 (23rd July 2019) - Sanzone, Alessandro; Mattiello, Sara; Garavaglia, Giulia Maria; Calascibetta, Adiel Mauro; Ceriani, Chiara; Sassi, Mauro; Beverina, Luca
Abstract : NewPiNap-750M π-surfactant enables unprecedented performances in the preparation of BTBT derivatives and other organic semiconductors by Suzuki-Miyaura coupling in water and at room temperature. Abstract : Micellar catalysis enables carrying out Suzuki–Miyaura couplings in water under exceptionally mild conditions. Extension of such a protocol to the sustainable synthesis of highly conjugated, poorly soluble materials like [1]benzothieno[3, 2- b ][1]benzothiophene (BTBT) requires redesigning of the surfactants employed. The here reported new naphthalenediimide containing amphiphilic derivative, PiNap-750M, features unprecedented performances in the preparation of this and other relevant classes of organic semiconductors in water and at room temperature.